2020
DOI: 10.3390/su13010125
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Answers to Food Loss and Waste Management in Spain from a Holistic Nutritional and Economic Approach

Abstract: The generation of food loss and waste (FLW) is a global problem for worldwide politics. About one-third of the food produced ends up in the rubbish before it is consumed. For this reason, it is essential to design and implement new strategies along the food supply chain (FSC) with the aim of reducing this FLW at each stage. However, not only mass quantification should be considered, but also economic and nutritional performance. The novelty of this study is the definition of a methodology based on the “distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Through the analysis of the diagram of sustainability in the agro-industry, shown in Figure 3, it is possible to verify that the FSC is composed by farming (production), postharvest, processing, distribution, and consumption, and their different goals should be taken in consideration through the circular economy and FLW reduction [29,30]. The political and cultural aspects must be considered in addition to the three pillars of a sustainability society, the environment, and the economy in the agri-food sector.…”
Section: Logistics: Product and Process Developmentmentioning
confidence: 99%
“…Through the analysis of the diagram of sustainability in the agro-industry, shown in Figure 3, it is possible to verify that the FSC is composed by farming (production), postharvest, processing, distribution, and consumption, and their different goals should be taken in consideration through the circular economy and FLW reduction [29,30]. The political and cultural aspects must be considered in addition to the three pillars of a sustainability society, the environment, and the economy in the agri-food sector.…”
Section: Logistics: Product and Process Developmentmentioning
confidence: 99%
“…The GHG emissions derived from FLW treatment only include those occurring in the stages that dispose of these organic residues in urban environments. Hence, carbon emissions linked to FLW treatment in the production stage were excluded from the system boundaries given their heterogeneous disposal in rural, peri-urban or industrial contexts in which traceability of these residues is unclear (Margallo et al, 2020).…”
Section: Ghg Emissions In Food Loss and Waste (Flw) Production And Tr...mentioning
confidence: 99%
“…Moreover, Hoehn et al [37] suggested meat FLW as the category with the highest embodied energy loss, which was much higher than fruit or vegetables. Recently, a new work developed by Laso et al [50] highlighted vegetables, fruits, and cereals as the categories less efficient in terms of generated FLW mass. In this work, if the total of the three indicators (WF, GWP, and NFLW) of each FLW category assessed eggs, cereals, meat, and vegetables then the categories highlighted as the most important when developing strategies for FLW management in Spain, by policy-makers, achieved compliance with the five SDGs assessed.…”
Section: Sdg-food Index In the Spanish Food Supply Chainmentioning
confidence: 99%